LAW ENFORCEMENT AGAINST REFUGEES WHO VIOLATE THE RULES IN PEKANBARU CITY BASED ON PRESIDENTIAL REGULATION NUMBER 125 OF 2016 CONCERNING HANDLING OF REFUGEES FROM ABROAD - Fahli, Zul; Triana, Yeni; Harahap, Irawan (EKSEKUSI, 2025)
ABSTRACT Article 30 paragraph (2) of Presidential Regulation Number 125 of 2016 concerning Handling of Refugees from Abroad regulates sanctions for special placement/isolation of refugees who violate accommodation regulations." The purpose of the study is to analyze law enforcement against refugees who violate the rules in Pekanbaru City based on Presidential Regulation Number 125 of 2016; To analyze the inhibiting factors; To analyze efforts to overcome the obstacles. The research method is sociological legal research, legislative and case approaches; the research location is the National Unity and Politics Agency of Pekanbaru City; population and samples from relevant sources; data sources are primary, secondary and tertiary; data collection techniques are observation, structured interviews and document/literature studies; data analysis is qualitative with inductive conclusion drawing. Law enforcement has not been implemented properly, especially from 2020 to 2024, as evidenced by the fact that special placement sanctions have not been applied to refugees who violate. Second, inhibiting factors are legislative factors; law enforcement officers/government, community, facilities. facilities and culture.Keywords: Refugees, Presidential Regulation, Pekanbaru ABSTRAK Pasal 30 ayat (2) Peraturan Presiden Nomor 125 Tahun 2016 tentang Penanganan Pengungsi dari Luar Negeri mengatur sanksi penempatan khusus/ pengisolasian terhadap pengungsi yang melanggar tata tertib akomodasi.” Tujuan penelitian ialah Untuk menganalisis penegakan hukum terhadap pengungsi yang melanggar aturan di Kota Pekanbaru  berdasarkan Peraturan Presiden Nomor 125 Tahun 2016; Untuk menganamisis faktor yang menghambatnya; Untuk menganalisis upaya mengatasi hambatannya. Metode penelitiaan ialah penelitian hukum sosiologis, pendekatan perundang–undangan dan kasus; lokasi penelitian yaitu Badan Kesatuan Bangsa dan Politik Kota Pekanbaru; populasi dan sampel dari narasumber relevan; sumber data ialah primer, sekunder dan tersier; teknik pengumpulan data ialah observasi, wawancara terstruktur dan studi dokumen/kepustakaan; analisis data ialah kualitatif dengan penarikan  kesimpulan induktif. Penegkan hukumnya belum dilaksanakan dengan baik terutama tahun 2020 sampai 2024 dibuktikan terhadap para pengungsi yang melanggar, sanksi berupa penempatan secara khusus belum diterapka. Kedua, Faktor yang menghambat ialah Faktor perundang-undangan; aparat penegak hukum/ pemerintah, masyarakat, sarana. fasilitas dan kebidayaan.Kata Kunci: Pengungsi, peraturan Presiden, Pekanbaru